César Dávila Andrade, la noche y la bohemia quiteña (Legados: Centenario del natalicio de César Dávila Andrade, el Faquir, Cuenca, 1918-Caracas, 1967) - Espinosa Apolo, Manuel Agustín (2018)
What does being a bohemian imply, and how can the relationship of Ecuadorian poet César Dávila Andrade (called The Faquir by his closest friends) with the night, the underground world, and with alcohol be characterized and understood? This is the question this article tries to answer. The research in which it relies considers sources as memoirs and oral testimony of relatives and friends close to the poet; biographic articles and academic studies of Dávila’s works. The author analyzes the poet’s life in a critical period: his stay in Quito between 1944 and 1949, time in which he, along with other writers and artists living or born in Quito, leaded an intense and hallucinating bohemia. In that disordered experience, The Fakir turned to be one of Quito’s popular characters, turning his life into a legend woven with anecdotes that delight, move, and induce reflection up to this day. All these anecdotes emphasize the poet’s enthrallment and solidarity with the urban underground of Quito, his intimate relationship with the night and his unique alcoholic proclivity.